2018
DOI: 10.4103/ua.ua_94_17
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted ureteral reconstruction – current status and future directions

Abstract: Robotic surgery in the treatment in certain urological diseases has become a mainstay. With the increasing use of the robotic platform, some surgeries which were historically performed open have transitioned to a minimally invasive technique. Recently, the robotic approach has become more utilized for ureteral reconstruction. In this article, the authors review the surgical techniques for a number of major ureteral reconstuctive surgeries and briefly discuss the outcomes reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
0
5
0
2
Order By: Relevance
“…Multiple studies 16–18 have demonstrated comparable outcomes with a reduction in operating time for the robotic approach compared to open pyeloplasty surgery, the relative ease of suturing being the key advantage 1 . Data on RAS ureteric reimplant surgery demonstrates similar complication rates, re‐stricture rates and operative times but with decreased blood loss and length of stay 19,20 . Compared to conventional open surgery, RAS surgery generally results in reduced wound related morbidity 21 .…”
Section: Application Of Ras In Reconstructive Urologymentioning
confidence: 99%
“…Multiple studies 16–18 have demonstrated comparable outcomes with a reduction in operating time for the robotic approach compared to open pyeloplasty surgery, the relative ease of suturing being the key advantage 1 . Data on RAS ureteric reimplant surgery demonstrates similar complication rates, re‐stricture rates and operative times but with decreased blood loss and length of stay 19,20 . Compared to conventional open surgery, RAS surgery generally results in reduced wound related morbidity 21 .…”
Section: Application Of Ras In Reconstructive Urologymentioning
confidence: 99%
“…Лікування пацієнтів з мультифокальним нирково-клітинним раком є одним з найбільш складних завдань, оскільки стратегія лікування таких хворих досі остаточно не вирішена, а вибір метода лікування мультифокального раку є джерелом наукових дебатів. При цьому мультифокальність залишається одним із відносних протипоказань до ОЗХ [2].…”
Section: вступunclassified
“…Пластика мочеточника тубуляризованным лоханочным лоскутом является относительно редкой опцией уретеральной реконструкции [1,2]. Данный хирургический подход позволяет заместить протяженные дефекты верхней трети мочеточника, а в отдельных случаях и весь мочеточник [3,4].…”
Section: Introductionunclassified
“…This has been overshadowed by the introduction of Robotic assisted surgeries in recent time with added advantages of making the procedure simple and decreased peri-operative morbidity. The robotic platform has the bene t of better threedimensional visualization, tremor reduction, more precision and ner control, less blood loss, and shorter hospital stay 1 .…”
Section: Introductionmentioning
confidence: 99%